A Short-Term Effect of Wearable Technology-Based Lifestyle Intervention on Body Composition in Stage I–III Postoperative Breast Cancer Survivors - Zhou, Changming; Mo, Miao; Wang, Zezhou; Shen, Jie; Chen, Jiajian; Tang, Lichen; Qiu, Jiajia; Ling, Yiqun; Ding, Huiping; Jiang, Qin; Wang, Hui; Shao, Zhimin; et al. (Frontiers in Oncology, 2020)
Background and aim: A healthy body composition can improve the prognosis of breast cancer survivors. The study aimed to describe the body composition profile of breast cancer survivors and find out whether a short-term (3 months) wearable device–based lifestyle intervention had an effect on patients’ body weight and body composition. Methods: A before-and-after study was conducted on patients with stage I–III postoperative breast cancer, aged 18–70 years. Body composition was analyzed at baseline and then patients went for a health education program. A wearable activity tracker and a goal of calorie consumption based on each individual’s weight were provided to each participant, and they were required to be equipped for 90 days. After 3 months, the body composition was analyzed again. Results: Of 113 patients who completed the study, 65.49% showed a normal body mass index (BMI) at baseline assessment, 71.68% had a body fat percentage of more than 30%, and 41.59% had less skeleton muscle mass. During the intervention, the daily step count was 8851.28 ± 2399.31, and 59.21% reached the set goal calorie consumption. After a 3-month intervention, patients had a significant reduction in body weight), fat mass, BMI, body fat percentage, and visceral fat area, but not in protein mass and skeleton muscle mass. Patients with different age, molecular classification, and therapy benefited from the intervention. Conclusion: Wearable technology with body composition analysis and health education for breast cancer survivors may help reduce the weight and improve body composition even in a short time.